The Effectiveness of Brain GYM on Improving Ability Motoric Smooth in Children Age Preschool in Kindergarten - Fardila Elba; Hafizah Che Hassan (Yayasan Media Utama Sains, 2025)
Background Back : Development motor fine is one of the aspect important in grow flower child age preschool that plays a role in support readiness learning and activities everyday . However , it is not all child experience optimal development so required proper stimulation . One of the methods that can used is exercise brain (brain gym), namely a series movement simple with purpose optimize function brain . Purpose Research : Research This aim For know effectiveness of Brain Gym on development motor smooth on children ages 3–5 years in the work area Subdistrict Batam City. Research methods​ This use pre- experimental design with one-group pretest-posttest approach . Sample A total of 31 children were taken use total sampling technique . Measurement development motor fine done using KPSP before and after intervention . Data analysis was carried out with paired sample t-test. Results: Research results show existence improvement development motor fine after given brain gym intervention . Before intervention , partly big child is in the category development doubtful (64.5%), whereas after intervention all over children (100%) are in the category in accordance development . Statistical test results show p -value = 0.000 (<0.05), which means there is influence significant effect of brain gym on development motor fine child . Conclusion: research This show that Brain Gym is effective in increase development motor fine child age preschool . Therefore that , Brain Gym can recommended as method stimulation development children in the neighborhood education and public.